Azfilla Sdn. Bhd. / Nor Azura Osman ... [et al.] - Osman, Nor Azura; Musa, Siti Nor Laila; Mohd. Ariff, Nurul Azura; Mior Abdullah, Rafidah (2001)
AZFILLA SDN BHD is a company that is productive in the nation’s industrial field. Our company sells books and stationery. We also provide special service to our customers, such as borrowing for the books. AZFILLA SDN BHD have four partners in the company and every partner holds about 25% of share. Our business are based on the beginning capital is about RM 750000 and about RM 500000 is loaned from Bank Rakyat. AZFILLA SDN BHD will ensure that is service quality will satisfy our customers and fulfill their taste with all the latest product. We estimate that this business will become successful in 2 to 5 years because our country, Malaysia is now heading forward into an era education development, which is moving fast towards 2020. AZFILLA SDN BHD is located in Alor Setar, Kedah. Our company address is WISMA D.T.C, Jalan Sultan Badlishah, 05000 Alor Setar, Kedah. The position of our company is very strategic because Alor Setar is known as town centre of Kedah Alor Setar also has many secondary and primary school. So, the place will be where the student gathered together to getting any types of book. Beside that, AZFILLA SDN BHD also prepared the types of book for the student of higher institution.